Near-complete phase transfer of single-wall carbon nanotubes by covalent functionalization - Kakade, Bhalchandra A.; Patil, Sanjay; Sathe, Bhaskar; Gokhale, Suresh; Pillai, Vijayamohanan (Journal of Chemical Sciences, 2008)
We describe here an efficient phase transfer of single wall carbon nanotubes (SWNTs) from aqueous to non-aqueous media using a unique amide functionalization route, where water soluble SWNTs (2.6 mg/mL) are effectively transferred to solvents like chloroform, toluene and CS(2). A maximum of 30 wt% of oxygenated groups have been generated on the side walls by rapid microwave treatment, leading to a solubility of more than 2.6 mg/mL in water. Approximate surface amine coverage of 50% has been accomplished after oxalyl chloride treatment as inferred from thermogravimetry and X-ray photoelectron spectroscopy by controlling several key parameters associated with the extent of functionalization including purity of the sample, temperature and time.
Keywords: Carbon nanotubes; microscopy; Microwave; Nanostructures; solubility of SWNTs

CVD synthesis of highly graphitized single-walled carbon nanotubes using nitrogen-pretreated Fe-Mo/MgO catalyst - Patil, Gaurav; Sarode, Chetan; Patil, Rahul; Gokhale, Suresh (Chemistry Letters, 2012)
Single-walled carbon nanotubes (SWNTs) with highly graphitized structure were synthesized by thermal chemical vapor deposition using an improved nitrogen-pretreated Fe-Mo/MgO catalyst. The effects of nitrogen pretreatment of Fe-Mo/MgO on the structure and properties of SWNTs were studied by TEM, Raman spectroscopy, and TGA. The investigations revealed that the nitrogen pretreatment of the catalyst promoted the growth of SWNTs. It also enhanced the structural features and thermal properties of SWNTs.

CVD synthesis of graphene nanoplates on MgO support - Jugade, Ravin M.; Sharma, Shalini; Gokhale, Suresh (Materials Science-Poland, 2014)
Synthesis of graphene directly on MgO has been carried out and the structural properties of the obtained material have been investigated. Few-layered graphene was produced by simple thermal decomposition of methane over MgO powder at 950 A degrees C in a CVD reactor. The samples were purified by 10 N HNO3 treatment, and studied by TEM, Raman spectroscopy, EDAX and SEM. TEM clearly indicated the formation of graphene. EDAX showed that the purified sample contained only carbon and no traces of MgO. The characteristic Raman features of graphene were also seen as D-band at 1316 cm(-1), G-band at 1602 cm(-1), and a small 2D-band at 2700 cm(-1) in the Raman spectra. The strong D-band suggests that the graphene possess large number of boundary defects. The small 2D-band indicates the formation of few-layered graphene.
Keywords: graphene; magnesium oxide; nanographene

Low-temperature sintering and microwave dielectric properties of Zn2SiO4 ceramic added with crystalline zinc borate - Chaware, Varsha; Deshmukh, Ravindra; Sarode, Chetan; Gokhale, Suresh; Phatak, Girish (Journal of Electronic Materials, 2015)
The physical and dielectric properties of composites of known microwave materials, Zn2SiO4 and Zn3B2O6, prepared by solid-state reaction, were investigated with the purpose of developing a low-loss dielectric material for low-temperature co-fired ceramic applications. An off-stoichiometric phase of Zn2SiO4 with extra SiO2 was used to avoid the occurrence of unreacted ZnO. During sintering, zinc borate was found to partially react with residual SiO2 to form Zn2SiO4. The residual zinc borate was converted to a boron-rich glassy phase which helped to reduce the sintering temperature of the composite. Good relative sintering density (> 90%) at temperatures below the melting temperature of zinc borate is indicative of a sintering mechanism of diffusion-based mass transfer. Composites containing 15 wt.% zinc borate, 2.5 wt.% lithium carbonate and 20 wt.% zinc borate in zinc silicate had dielectric constants of 6.8 and 6.1, quality factors (Qxf) of 48,800 and 94,300 GHz when sintered at 900A degrees C and 950A degrees C, respectively. These quality factor results are close to the best values reported for zinc silicate at these sintering temperatures.
Keywords: dielectric constant; LTCC; quality factor; sintering density; zinc borate; zinc silicate

Laser shielding and thermal ablation characteristics of resorcinol formaldehyde/boronnitride composites for thermal protection systems - Daniel, Alex; Badhe, Yutika; Srikanth, Ivaturi; Gokhale, Suresh; Balasubramanian, Kandasubramanian (Industrial & Engineering Chemistry Research, 2016)
Resorcinol formaldehyde (RF) composites were modified by incorporating different weight ratios of hexagonal boron nitride (h-BN) through a novel in situ polymerization technique. Temperature modulated SAXS was used to understand the changes in polymer network due to h-BN addition. The ablation performance of RF BN composites was evaluated by pulsed laser and oxyacetylene torch tests. Linear ablation resistance under oxyacetylene conditions improved by 18%. Laser ablation resistance increased by 44%. The reasons for improved ablation resistance for RF BN composites were studied using XRD, FTIR, and XPS methods which indicated that h-BN undergoes phase transformation at higher temperatures and also displays typical floral assimilation leading to significant energy consumption. This results in improved ablation resistance. These findings could lead to fabrication of RF BN based thermal protection systems (TPS) having better protection capabilities.

Sunlight assisted improved photocatalytic degradation of rhodamine B using Pd-loaded g-C3N4/WO(3)nanocomposite - Alman, Vidya; Singh, Kirti; Bhat, Tejasvinee; Sheikh, Arif; Gokhale, Suresh (Applied Physics A-Materials Science & Processing, 2020)
Effective photocatalytic degradation of organic toxic dyes from industrial effluents using low-cost nanomaterials as a photocatalyst under sunlight promises for water purification and environmental recovery. The present work is focused on the synthesis of Palladium (Pd) loaded g-C3N4/WO(3)nanocomposite using a facile method and its photocatalytic degradation of Rhodamine B (RhB) using under sunlight. The results of the photocatalytic dye degradation experiment show that Pd loaded g-C3N4/WO(3)nanocomposite photocatalyst degrades 98% of RhB in 40 min of sunlight illumination. This remarkable photocatalytic degradation performance of Pd loaded g-C3N4/WO(3)nanocomposite mainly attributed due to their intrinsic photocatalytic activity and co-existence of enhanced light absorbance and efficient charge transfer process in between the g-C3N4/WO(3)heterojunction. The durability testing experiments indicate that Pd loaded g-C3N4/WO(3)nanocomposite photocatalyst could be effectively reused and possesses high photochemical structural stability even after several recycle process. Present experimental results demonstrated highly encouraging photo-degradation response of Pd loaded g-C3N4/WO(3)nanocomposite photocatalyst at outdoor conditions paves the way for the development of energy conversion and environmental remediation process.
Keywords: Nanocomposite; Palladium loading; Photocatalysis; Photodegradation; Rhodamine B; Sunlight

Mechanical properties of anodic titanium dioxide nanostructures - Kulkarni, Mukta; Sepitka, Josef; Junkar, Ita; Bencina, Metka; Rawat, Niharika; Mazare, Anca; Rode, Chandrashekhar; Gokhale, Suresh; Schmuki, Patrik; Daniel, Matej; Iglic, Ales (Materiali in Tehnologije, 2021)
Highly ordered and uniform titanium dioxide (TiO2) nanotubes (NTs) with different morphologies (15 nm, 50 nm and 100 nm in diameter) were prepared by the electrochemical anodization of Ti substrates. The TiO2 NTs' surface properties were characterized by X-ray diffraction (XRD) spectroscopy, Raman spectroscopy, scanning electron microscopy (SEM) and atomic force microscopy (AFM). The elastic modulus (E) and the Vickers hardness (HV) of the Ti foil and of the different-morphology TiO2 NTs were evaluated with the nano-indentation technique. E and HV increase with the decreasing length/diameter of the NTs, meaning that NTs with smaller diameters are more resistant to mechanical wear. The elastic modulus of the TiO2 NTs with 15-nm and 50-nm diameters is similar to that of the human bone.
Keywords: Elastic modulus; mechanical properties; titanium dioxide (TiO2) nanotubes; Vickers hardness